De la aritmética práctica en el Perú, siglos XVI-XVII. Una aproximación - Luque L., Juvenal (2020)
This research seeks to present some aspects of colonial practical arithmetic during the XVI-XVII centuries that was the basis for understanding the arithmetic of colonial coins, the turn of commerce, etc. In this period is where various sectors of the economy felt the need for the help of arithmetic for the fast, accurate and safe turn of their businesses that rested in various currencies or other units. With this study is intended not only to present some aspects of that arithmetic and find existing links with the economy, we will advance some characteristics of the colonial arithmetic practice with the description of some of its rules to see its practical application everyday. It will be presented how the consolidation of mathematical practicism served as a means of disseminating its rules through extra educational institutions, daily exercise and oral transmission, as well as printed texts, copies of printed material and manuscripts, in general, all due to private effort. As sources have been used printed texts on the subject in Peru, America or Spain and existing manuscript documents in Lima.